2019
DOI: 10.1155/2019/4630490
|View full text |Cite
|
Sign up to set email alerts
|

Body Mass Index and Primary Headache: A Hospital-Based Study in China

Abstract: Objective. Primary headache and obesity are highly prevalent disorders in the general population. Although many studies have reported an association between the two, there is still no overall comprehension about this relationship. To gain a more accurate understanding in this regard, we analyzed data from a 2011 cross-sectional study in Chongqing, China. Methods. Patients with a chief complaint of headache were administered a headache questionnaire and diagnosed by neurology doctors in accordance with the Inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 29 publications
1
16
1
Order By: Relevance
“…Some epidemiological studies have shown that several risk factors, including sex [7], body mass index (BMI) [8], smoking [9], family history [10], and climate [11] might be associated with primary headache disorders. Despite the lower prevalence in China, the risk factors are similar to those reported for other countries [12][13][14]. In a previous study in North China, we found that the prevalence of primary headache disorders in nurses was significantly higher than that in the general population (45.3% vs. 23.8%) [15].…”
Section: Introductionsupporting
confidence: 83%
“…Some epidemiological studies have shown that several risk factors, including sex [7], body mass index (BMI) [8], smoking [9], family history [10], and climate [11] might be associated with primary headache disorders. Despite the lower prevalence in China, the risk factors are similar to those reported for other countries [12][13][14]. In a previous study in North China, we found that the prevalence of primary headache disorders in nurses was significantly higher than that in the general population (45.3% vs. 23.8%) [15].…”
Section: Introductionsupporting
confidence: 83%
“…Huang and teammates (2019) also reported in their study that mean age of the patients in EM group was 40.71+20.34 years while in CM group was 46.9+16.89 years (P=0.001). [12] In our study educational level was found better among EM group patients but Huang and coworkers (2018) asserted in their study that patients in CM group had better educational level than EM group. [11] High blood pressure could be a major cause of migraine.…”
Section: Resultscontrasting
confidence: 55%
“…A study done by Huang and teammates (2019) also showed comparable results who confirmed that in EM group 18.9% patients and in CM group 29.8% patients were hypertensive (P=0.005). [12] Study further disclosed that patients in both groups had severe pain. The mean pain intensity in EM group was 4.6+2.41 and in CM group was 4.3+2.51 (P=0.713.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Individuals who were overweight showed a higher prevalence of headache compared to the obese individuals. Similarly, a Chinese study found that chronic migraine and a tension-type headache were more common in higher BMI patients [ 23 ]. Likewise, individuals being obese and having episodic headaches were five times more likely to develop chronic daily headaches than normal weight individuals [ 24 ].…”
Section: Discussionmentioning
confidence: 99%